The intra-articular pure-platelet rich plasma as a disease-modifying treatment for patients suffering from knee osteoarthritis - Jifeel, Waleed M; Alzamily, Ajil A; Abdulabbas Alsalman, Ihsan (Vojenské zdravotnické listy, 2023)
Background: The knee is the predominant weight-bearing joint affected by osteoarthritis, and knee osteoarthritis (KOA) is the 11th significant cause of disability. As life expectancy has increased, the need for knee replacement procedures has grown, putting a major financial burden on patients and healthcare systems. Intra-articular (IA) injection of platelet rich plasma (PRP) promises to be a potential method in research for the more preservative and biological strategies to treat this chronic degenerative condition. PRP has expected to contain a high number of growth factors and proteins involved in tissue repair mechanisms.Aim: This study aimed to determine the effect of intra-articular injections (IAIs) pure-PRP and their dosage regimen efficacy in patients with mild and moderate knee OA.Material and method: This study included 33 patients (11 male and 22 female). The patient groups included 16 with mild and 17 with moderate knee osteoarthritis. With ages ranged from 32 to 66 years old. These patients were divided into three groups based on dosage (12 received a single injection, 11 received a double injection, and 10 received a triple injection), with a two-week interval between injections. The outcome was measured using WOMAC index for pain, stiffness, and daily functional limitation, as well as laboratory testing for TNF-alpha using the Eliza technique. All the patients were assessed at baseline and after three months of injection. The study was designed as non-randomized controlled trial study during November 2021 to May 2022 at Al-imam Ali hospital, Babylon governorate, Iraq.Results: Regarding severity, In both mild and moderate knee osteoarthritis, serum TNF-alpha was significantly lower after treatment (p < 0.001). All WOMAC scores were showed significantly lower levels after treatment with pure-PRP as compared with their levels before treatment (p ≤ 0.001, Regarding the number of injections, all patients who received a single injection, double injections, and triple injections showed a significant decrease in the serum TNF-alpha and WOMAC scores (p 0.05) in both mild and moderate patients. The triple injections were more effective than double and single injections.Conclusions: In conclusion, the treatment with pure-PRP was safe and satisfactory for patients in terms of relieving clinical symptoms. The WOMAC scores has indicated that improvement in pain relief for patients after injection and could act as an anti-inflammatory, as inflammatory marker TNF-alpha was reduced after injection, and there was a superior outcome to increasing dose numbers, as triple injection gave a positive outcome in both mild and moderate KOA when compared to single and double injection.
Keywords: dospělí; Statistics as Topic; Female; statistika jako téma; Health Status Indicators; Adult; Tumor Necrosis Factor-alpha; ženské pohlaví; Therapeutic Index; terapeutický index; lidé; ukazatele zdravotního stavu; injekce intraartikulární; Injections, Intra-Articular; artróza kolenních kloubů; plazma bohatá na destičky; Platelet-Rich Plasma; TNF-alfa; Male; Osteoarthritis, Knee; lidé středního věku; mužské pohlaví; Middle Aged; Humans